2013
DOI: 10.1186/1743-422x-10-37
|View full text |Cite
|
Sign up to set email alerts
|

Lineage shift in Indian strains of Dengue virus serotype-3 (Genotype III), evidenced by detection of lineage IV strains in clinical cases from Kerala

Abstract: BackgroundLocal epidemiology of Dengue is defined by the genetic diversity of the circulating Dengue virus (DENV) strains. This important information is not available for the virus strains from most parts of the Indian subcontinent. The present study focused on the genetic diversity of the serotype 3 DENV strains (DENV-3) from India.ResultsA total of 22 DENV-3 strains identified by reverse-transcription PCR analysis of serum samples from 709 patients were studied. These samples were collected over a period of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…However, majority of our sequences (23/32), diverged and clustered together to form a new lineage 'GIVc', exhibiting minimum nucleotide divergence of 3%-4% with the closest GIVb strains (Delhi-2003 andKerala-2010). In some of the previous Indian dengue outbreaks, emergence or shift of new lineages has been documented in other serotypes/genotypes such as; GIII of DENV-1 in 2006 outbreaks in Delhi (Kukreti et al, 2008) and GIII of DENV-3 in Kerala during 2008-2011 epidemics (Manakkadan et al, 2013). It was suggested that high evolutionary rates of certain DENV genotypes and their increased transmission rate between several human hosts in hyperendemic settings may contribute to the emergence of new lineages (Waman et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, majority of our sequences (23/32), diverged and clustered together to form a new lineage 'GIVc', exhibiting minimum nucleotide divergence of 3%-4% with the closest GIVb strains (Delhi-2003 andKerala-2010). In some of the previous Indian dengue outbreaks, emergence or shift of new lineages has been documented in other serotypes/genotypes such as; GIII of DENV-1 in 2006 outbreaks in Delhi (Kukreti et al, 2008) and GIII of DENV-3 in Kerala during 2008-2011 epidemics (Manakkadan et al, 2013). It was suggested that high evolutionary rates of certain DENV genotypes and their increased transmission rate between several human hosts in hyperendemic settings may contribute to the emergence of new lineages (Waman et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Lineage replacement in dengue viruses has been reported in many studies [ 25 33 ] including India. A lineage replacement event where lineage III replaced lineage I was detected in 2012–2014 in Delhi.…”
Section: Discussionmentioning
confidence: 99%
“…This particular geographic situation may impact dengue epidemiology in that it may favor the cross boarder movement of viral isolates. A better understanding of DENV movement is now considered as a key point as emergence of new strains or genotypes have been associated with increased clinical severity [12] , [13] , [14] . Our study demonstrated that during the 2012–2013 epidemic, both DENV-3 genotypes II and III detected in Vientiane city were associated with death.…”
Section: Discussionmentioning
confidence: 99%